Relationship between muscle strength, power and stiffness and running economy in trained male runners - Dumke, C. L.; Pfaffenroth, C. M.; McBride, J. M.; McCaulley , G. O. (International Journal of Sports Physiology and Performance, 2010)
Purpose: In this study, a comparison was made between muscle strength, power and muscle and tendon (kmand ktrespectively) stiffness of the triceps surae muscle group and running economy (RE) in trained male runners. Methods: Twelve well-trained male runners (age = 21 ±2.7 y, height = 178.1 ± 7.1 cm, body mass = 66.7 ±3.2 kg, VO2max = 68.3 ±4.3 mL/kg·min, 5000-m time = 15:04 min:s) underwent passive tiffness testing using a free oscillation method. Muscle strength was determined via a maximal isometric squat test and power determined via a maximal countermovement jump (CMJ). On a separate day, subjects performed an incremental treadmill test and their RE, lactate threshold, and VO2max were determined. Fingertip blood lactate was determined at the end of each 3-min stage. Lactate threshold was defined as a nonlinear increase in lactate accumulation. Results: A statistically significant correlation was found between kmand VO2at stage 6 (r = -0.69, P = .01). In addition, statistically significant correlations were observed between CMJ peak force production and VO2 at stage 2 (r = .66, P = .02), stage 3 (r = .70, P = .01), and stage 4 (r = .58, P = .04). No other statistically significant correlations were observed. Conclusion: These data suggest that greater muscle stiffness and less power are associated with greater RE. Future study in this area should focus on determining the mechanisms behind this relationship and how to best apply them to a running population through training techniques.